Mothers balancing work and family: the associations with emotional well-being, sleep–wake problems and the role of basic needs - Rosalia Olivieri; Alessandro Lo Presti; Sebastiano Costa; Lucia Ariemma; Marco Fabbri (BMC Psychology)
Abstract Background The transition to motherhood involves significant changes, extending from pregnancy to the early years of a child's life. This period, characterized by multiple stressors and adjustments, can profoundly impact maternal well-being. For this reason, the aim of this study was to investigate the associations between work-family balance, need satisfaction, depression, anger, vitality and sleep–wake problems, using Self-determination Theory (SDT) as a theoretical framework. Methods Participated in this study 218 working mothers in Italy with children aged between 1 and 36 months. Using a correlational design, SEM with latent variables was used to test an integrative model. Results Results revealed significant positive associations between work-family balance and need satisfaction, and vitality, and negative direct associations of need satisfaction with sleep–wake problems, depression, and anger. Indirect associations were also visible between work-family balance and psychological outcomes through need satisfaction. Conclusions. Overall, findings underscore the importance of conditions that support the satisfaction autonomy, competence, and relatedness of working mothers during this critical life stage. These insights have implications for organizational policies and interventions aimed at supporting the mental health of working mothers.